PENGARUH KONSELING FARMASIS DAN KONDISI SOSIODEMOGRAFI TERHADAP KEPATUHAN DAN HASIL TERAPI DI PUSKESMAS PURWOKERTO SELATAN KABUPATEN BANYUMAS - , FAJRIN NOVIYANTO; , Prof.Dr, Sugiyanto, SU., Apt. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Patientâs understanding, knowledge, and obedience are expected to increase as the pharmacist gives useful and appropriate information to the patient. This research was done to find out the influence of pharmacistâs counseling and sociodemagraphys condition toward obedience and to know the relationship between obedience and therapy result of the patient at local government clinic of South Purwokerto in Bayumas Regency. This study was conducted using quasy experimental design. Retriveral of patient data prospectively conducted during the periode of January â March 2014. Patients were grouped randomly into two groups of different subjects, the patients who got counseling from pharmacist / researcher (intervention group) and those who did not get counseling (control group), followed by approximately one month observation of the obedience level and therapy result (blood pressure decline) of hypertension patient at local government clinic of South Purwokerto in Bayumas Regency. Data collection technique was done by doing interviews, and filling MMAS obedience questionnaires while the blood pressure data was obtained from medical record. There were 159 subjects of the research consisted of 78 (49.06%) subjects in control group and 81 (50.94%) subjects in intervention group. Wilcoxon test showed that there was significance difference in the end of MMAS with initial MMAS categories with the value p<0.05. Based on analysis using Chi-Square test showed that there was no significance difference of socio demographic in the end of MMAS with the value p>0.05. Counseling may have positive influence to the obedience of intervention group compared to the control group while also decreasing blood pressure in systolic and diastolic. There was significance relationship between the decrease of blood pressure and MMAS score of hypertension patient. Keywords: Hypertension, Counseling, MMAS, local government clinic.